Belonging and Othering in Research and Education: A Foreword - Rodriguez, Nurgul; Cruz, Fabielle Rocha; Ferguson, Warren; Coombs, Emily (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
The 2024 edition of the Graduate Studies Faculty in Education Journal emerges from Tapestry 2024: Belonging and Othering in Research and Education, a symposium exploring the intricate dynamics of inclusion and exclusion in educational and research contexts. This foreword reflects on the conference’s central themes through a personal lens, highlighting the profound impact of identity, culture, and lived experience in shaping scholarly and pedagogical work. Drawing on the metaphor of a tapestry, it underscores the richness of diverse narratives and methodologies—from autoethnography to community-based research—that challenge dominant paradigms and reimagine education as a site of belonging, recognition, and justice. Emphasizing reflexivity, vulnerability, and the transformative potential of embracing difference, the foreword invites readers to consider their positionalities and roles in fostering inclusive practices. The contributions in this volume call for sustained, collaborative efforts to dismantle systems of othering and co-create educational spaces grounded in equity, respect, and relationality.